2012
DOI: 10.1017/s1047951112000613
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cardiac functions with Doppler echocardiography in children with Down syndrome and anatomically normal heart

Abstract: Despite an apparently normal heart, children with Down syndrome may have silent disturbed cardiac functions, which may be detected by two-dimensional or tissue Doppler echocardiography. This may have an important clinical implication, especially before involving Down syndrome children in surgery or strenuous exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 21 publications
(31 reference statements)
4
27
0
Order By: Relevance
“…Our study agreed with the results of these reports, which indicated a significantly higher heart rate in Down syndrome subjects than in normal children (21)(22)(23). This finding is considered to be due to the autonomic cardiac dysfunction occurring at the central brain stem site as a result of a genetic disorder (24).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our study agreed with the results of these reports, which indicated a significantly higher heart rate in Down syndrome subjects than in normal children (21)(22)(23). This finding is considered to be due to the autonomic cardiac dysfunction occurring at the central brain stem site as a result of a genetic disorder (24).…”
Section: Discussionsupporting
confidence: 93%
“…In a similar study conducted by Al-Biltagi, these rates were reported to be 1.57 and 1.04, respectively (21). Both these ratios were lower than those of normal subjects in other reports that found a similar difference (21,22).…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations